Personal Taxation, Pension Wealth, and Portfolio Composition - Hubbard, R. Glenn (The Review of Economics and Statistics, 1985)
This paper emphasizes the roles played by personal taxation and pension wealth in portfolio choice and composition. A theoretical discussion of the impacts of taxation and participation in social security and private pension systems on individual wealth allocation is followed by empirical evidence based on U.S. cross-section data. Both effects prove to be significant. Anticipated social security and private pension benefits exert a measurable influence on household portfolio allocation. Their omission from an asset demand model may lead to a misinterpretation of the impact of taxation on portfolio composition.